Peningkatan Keamanan Lingkungan Berbasis Internet of Think melalui Implementasi One Gate System di Desa Watugede - Subari; Rakhmad Maulidi; Jozua F. Palandi; Febry Eka Purwiantono (Jurnal Pemberdayaan Masyarakat, 2025)
The community service program conducted in Watugede Village, Singosari, aims to enhance environmental security through the implementation of Internet of Things (IoT) technology. The rapid population and economic growth in the Banjararum View housing area has posed serious security challenges, such as theft and robbery. To address these issues, the IoT Guard system was introduced, which integrates an ESP32 WiFi-based automatic barrier gate and CCTV cameras for real-time monitoring. This system allows for remote access control via a mobile application and accurate activity log recording. The program was implemented through several stages, including socialization to the residents, training on system usage, technology implementation, and impact evaluation. The results of this activity indicate a significant improvement in environmental security, a decrease in crime rates, and increased community involvement in maintaining security. The sustainability of the program is designed by involving the community in the management and maintenance of the applied technology. Thus, this model is expected to be replicable in other environments to create safer and more controlled areas, providing long-term benefits for the community.